2005
DOI: 10.1002/jsfa.2301
|View full text |Cite
|
Sign up to set email alerts
|

Erucic acid content in some rapeseed/mustard cultivars developed in Bangladesh

Abstract: Seed samples of 21 indigenous and developed rapeseed/mustard cultivars (Brassica campestris, B. juncea and B. napus) were characterized for their fatty acid composition. Erucic acid was one of the main fatty acids, in proportions ranging from 21.59 to 51.57% followed by oleic acid ranging from 7.03 to 25.21%. The other major monounsaturated fatty acid was gadoleic acid, which accounted for 4.12-12.06%. The major polyunsaturated fatty acids were linoleic and linolenic acid, ranging from 11.79 to 16.89% and 6.29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Palmitic acid, a main saturated fatty acid, had a positive correlation with palmitoleic (0.797), linoleic (0.540), oleic (0.504), linolelaidic (0.404), and linolenic (0.337), and a negative correlation with arachidic (-0.387), behenic (-0.690), lignoceric (-0.721), and erucic (-0.764) acids among the saturated fatty acids, while stearic acid had a significant and positive correlation (0.862) with linoleic acid. Mortuza et al, (2006) also found a positive correlation of palmitic acid with gadoleic, linolenic, oleic, and linoleic acids, and a reverse correlation with erucic acid.…”
Section: Correlation Of Saturated and Unsaturated Fatty Acid Componentsmentioning
confidence: 70%
See 1 more Smart Citation
“…Palmitic acid, a main saturated fatty acid, had a positive correlation with palmitoleic (0.797), linoleic (0.540), oleic (0.504), linolelaidic (0.404), and linolenic (0.337), and a negative correlation with arachidic (-0.387), behenic (-0.690), lignoceric (-0.721), and erucic (-0.764) acids among the saturated fatty acids, while stearic acid had a significant and positive correlation (0.862) with linoleic acid. Mortuza et al, (2006) also found a positive correlation of palmitic acid with gadoleic, linolenic, oleic, and linoleic acids, and a reverse correlation with erucic acid.…”
Section: Correlation Of Saturated and Unsaturated Fatty Acid Componentsmentioning
confidence: 70%
“…The oil content of the B. rapa seed is 42% and the protein content is 25% (Khaleque, 1985). However, the oil content of currently cultivated B. rapa cultivars in Bangladesh contains high erucic acid (40%-45%) and high pungency due to high amounts of glucosinolates (300 parts per million or ppm) (Mortuza et al, 2006;Sultana et al, 2021). Consumption of erucic acid has been linked to myocardial lipidosis and heart lesions (Gopalan, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies employed saponification, acidification, methylation, thin layer chromatography, ozonization, and GC or gas‐liquid chromatography to determine erucic acid content. Another research reported internal standard was added during transesterification in order to quantify fatty acids exclusively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, both FAC results determined by NMR and conventional method through methylation and then chromatographic analysis [18] are comparable (Table 1). Previous studies employed saponification, acidification, methylation, thin layer chromatography, ozonization, and GC [9,21] or gas-liquid chromatography [12,22] to determine erucic acid content. Another research reported internal standard was added during transesterification in order to quantify fatty acids exclusively.…”
Section: Nmrmentioning
confidence: 99%
“…Low level of erucic acid in seed oil increases oleic acid, but also increases the linoleic and linolenic acids (Jagannath et al 2011). Presence of high erucic acid in edible oil is nutritionally undesirable as it is not metabolized and causes myocardial conductance and increased blood cholesterol (Renard and Mcgregor 1992;Mortuza et al 2005). The erucic acid is negatively correlated with oleic acid, therefore, the genotypes with low erucic acid coupled with high oleic acid can be developed.…”
mentioning
confidence: 99%